Primary infective spondylodiscitis caused by Lactococcus garvieae and a review of human L. garvieae infections - Chan, J. F. W. (Springer-Verlag, 2011)
We report the first case of primary infective spondylodiscitis due to Lactococcus garvieae, confirmed by 16S rRNA gene sequencing, in the absence of concomitant endocarditis in a patient with long-standing gastritis on famotidine. He responded to a 6-week course of ampicillin. The gastrointestinal tract is probably the source of infection.